How leadership behaviors influence the effects of job predictability and perceived employability on employee mental health – a multilevel, prospective study - Fløvik, Lise; Knardahl, Stein; Christensen, Jan Olav (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVES ': 'This study aimed to elucidate the potential moderating effect of fair-, empowering-, and supportive-leadership behaviors on the relationship between job predictability, future employability, and subsequent clinically relevant mental distress. ' ' METHOD ': 'The study had a full panel, prospective design, utilizing online, self-administered questionnaire data collected at two time points, two years apart. Fair-, empowering-, and supportive-leadership behaviors, job predictability and future employability were measured by the General Nordic Questionnaire for Psychological and Social Factors at Work (QPSNordic). Mental health was measured using the 10-item Hopkins Symptom Checklist (HSCL-10), with cut-off set to >1.85 to identify clinically relevant cases. As data were nested within work units, a multilevel analytic approach was chosen. ' ' RESULTS ': 'Individual-level direct effects: (i) higher levels of job predictability [odds ratio (OR) 0.83, 95% confidence interval (CI) 0.70–0.98], (ii) future employability (OR 0.83, 95% CI 0.74–0.93), (iii) fair- (OR 0.78, 95% CI 0.68–0.91), empowering- (OR 0.77, 95% CI 0.67–0.87), and supportive- (OR 0.71, 95% CI 0.61–0.81) leadership behavior, and (iv) the combination “quality of leadership” (OR 0.69, 95% CI 0.59–0.81) were significantly associated with a lower risk of reporting subsequent mental distress. Work-unit level direct effects: higher work-unit levels of fair- (OR 0.52, 95% CI 0.34–0.80) and empowering- (OR 0.61, 95% CI 0.40–0.94) leadership behaviors and quality of leadership (OR 0.54, 95% CI 0.34–0.87) were significantly associated with a lowered risk of subsequent mental distress. Cross-level interactions: No cross-level interaction effects were shown. ' ' CONCLUSIONS ': 'Leadership behaviors did not moderate the effects of job predictability and future employability on mental health. However, employees embedded within work-units characterized by fair, empowering and supportive leadership behaviors had a lower risk of subsequent mental distress.
Keywords: direct effect; employability; employee health; job insecurity; job predictability; leadership; leadership behavior; mental health; moderating; multilevel; organizational change; perceived employability; prospective study; psychosocial